Implementation of FTIR-Based Fingerprinting, Antioxidant Compounds Profiling by UHPLC-Q-Orbitrap HRMS, and Docking Study COVID-19 Inhibitor of Buas-Buas (Premna serratifolia) Leaf Extract from Pontianak Indonesia - Dini Hadiarti; Mahwar Qurbaniah; Ely Setiawan; Taufan Hari Sugara (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This research aims to profile the active antioxidant compounds from leaf extracts of Buas-buas (Premna serratifolia) growing in Pontianak of West Kalimantan (Indonesia) through a metabolomics approach and their activity as anti-COVID-19 candidates by molecular docking. In this study, P. serratifolia leaves were macerated and fractionated using solvents with different polarities. The extracts were then tested for antioxidant activity using the DPPH method, determined the total phenolic content (TPC), flavonoids (TFC), and steroids (TSC), and analyzed antioxidant the functional groups and compounds by Fourier Transform Infrared spectroscopy (FTIR) and Ultra High-Performance Chromatography UHPLC-Q-Orbitrap HRMS. The functional groups on antioxidant activity were determined by Principal Component Analysis (PCA) and Partial Least Square (PLS) regression. Based on a metabolomics approach, the PCA and PLS analysis shows that hydroxyl was the most active antioxidant from P. serratifolia leaves. UHPLC-Q-Orbitrap HRMS analysis showed the presence of scopoletin, esculetin, 7-hydroxycoumarine, matairesinol, hymecromone, and hexylresorcinol in the water fraction of P. serratifolia leaves. Molecular docking with 4YE6, 1OG5, and 3NRZ shows that matairesinol had the most potential as an antioxidant. Mataresinol and hexyresorcinol are phenolic compounds that have great potential as a COVID-19 inhibitor based on molecular docking with 5R81, 7CMD, and 6M2N.